First Grade of Secondary School Students Creativity in Solving PISA Question with Social Context - Shadiqoh, Sela Nur; Zubainur, C M (International Conference on Elementary Education, 2020)
Creativity in learning mathematics becomes a matter that really needs attention. Various learning approaches and strategies are suggested for developing creativity in mathematics, such as forming an open learning environment, integrating mathematics learning with other disciplines and providing a variety of open problems. At present, mathematics learning is very much emphasized on the involvement of a context, so students directly understand the usefulness of mathematics in their lives. Results The mathematical abilities of Indonesian students in the 2015 Programme for International Student Assessment (PISA) are still very low. This is due to the unfamiliarity of Indonesian students to solve questions equivalent to PISA with the involvement of a context. PISA assessment is one indicator of the success of a country's mathematics learning. Therefore, it has become a necessity for educators to consider the importance of involvement of PISA equivalents in learning mathematics starting in seventh grade in junior high school. This qualitative research involved twenty-five seventh grade students. Student creativity in solving PISA-equivalent questions can be trained by the teacher through interaction and dialogue between students and teachers. Student creativity in solving problems arises when the teacher is more open and appreciative of all student ideas